(untitled) (Conferencea, 2023)
Data leakage prevention (DLP) systems have become increasingly crucial in today’s data-driven world, where organizations must safeguard sensitive information from unauthorized access and inadvertent exposure. This article explores the development of DLP systems, their various types, and offers a comparison of related works in this field. By understanding the types and methods of DLP, organizations can better protect their valuable data assets.